Fertility diagnosis of soils cultivated with coffee Conilon in the southern state of Espírito Santo - Lang Burak, Diego; Ribeiro Passos, Renato; Cassa Duarte Venâncio, Felipe; Chierici Bernandes Rinaldi, Laís; da Silva, Sônia Maria; de Oliveira Roberto, Carlos Eduardo; Oliveira Rodrigues, Tamiris; de Oliveira Machado, Fabiano (Guará Journal, 2025)
The aim of this work was carry out the soil survey and diagnosis of the different levels of fertility in coffee farms. It was noted that the low levels of fertility for potassium and low soil base saturation can be constraints highest grain yield. The Cachoeiro Itapemirim and surrounded region have better natural soil fertility. From this diagnostic of soil fertility we can be identify regions that require other actions extension actions focused on facility of acquisition of nutrients potassium sources and lime sources.